2021
DOI: 10.1088/1402-4896/ac00e5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of joule heating and viscous dissipation on three dimensional flow of Casson model comprising temperature dependent conductance utilizing shooting method

Abstract: This report examines the flow of non-Newtonian fluids down a bilateral surface under the influence of a magneto-hydrodynamic effect that is applied in many fields seen in the applied sciences and has received the attention of researchers because of its vast usage. It is assumed that the movement of particles generated fluid due to the movement of walls in the light of horizontal and vertical directions. Thermal study is carried out by employing the contribution of Joule heating, viscous dissipation and radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Viscous dissipation being directly related to Nano fluid viscosity, considered to be the function of concentration consequently related to the temperature profile. Sohail et al [34] work based the three-dimensional flow behavior and observed the joule heating and viscous dissipation impacts for the Casson fluid model incorporating temperature reliant conductance with the aid of numerical approach namely shooting method. Abbasi et al [35] examined the ameliorated thermal efficiency along with optimized approach for the Copper Aluminum oxide under the influence of viscous dissipation and Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…Viscous dissipation being directly related to Nano fluid viscosity, considered to be the function of concentration consequently related to the temperature profile. Sohail et al [34] work based the three-dimensional flow behavior and observed the joule heating and viscous dissipation impacts for the Casson fluid model incorporating temperature reliant conductance with the aid of numerical approach namely shooting method. Abbasi et al [35] examined the ameliorated thermal efficiency along with optimized approach for the Copper Aluminum oxide under the influence of viscous dissipation and Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…Naseem et al (2021) discussed the numerical consequences of Soret and Dufour effects involving the role of thermal radiation over a stretching frame, including variable thermal conductivity. Sohail et al (2021) investigated the performance of entropy generation in a Casson fluid inserting the impact of Lorentz force. They discussed features of variable properties including various effects past a stretching frame.…”
Section: Introductionmentioning
confidence: 99%
“…Swain et al 21 initiated 3D nanoparticle aggregation of titanium nanoliquid with C 2 H 6 O 2 –TiO 2 via an exponentially elongated surface. The analysis of incompressible hybrid nanoliquid motion on a 3D rotating frame was presented by Xia et al 22 Sohail et al 23 examine non‐Newtonian liquid motion via bilateral surface under influence of MHD. Shoaib et al 24 developed 3D heat and mass transfer motion of hybrid nanoliquid via rotating disk.…”
Section: Introductionmentioning
confidence: 99%